2021
DOI: 10.1017/s095439452100020x
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing /s/ retraction: Sibilant variation and change in Washington D.C. African American Language

Abstract: Recent work has demonstrated an ongoing change across varieties of English in which /s/ retracts before consonants, particularly before /tɹ/ clusters (e.g., Lawrence, 2000; Shapiro, 1995; Stuart-Smith et al., 2019). Much of this work has focused on the social and linguistic distributions of /stɹ/ within single communities, without an examination of the broader sibilant space (e.g., /s/ and /ʃ/). Meanwhile, analyses across multiple corpora have shown that /s/ and /ʃ/ also show within-community variability, beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…( The realization of sibilants was measured by several acoustic parameters, including sibilant duration, F2 value at the onset of the following vowel, and spectral moments analysis of the target sibilant (Li 2009). Although /s/ and /ʃ/ can be identified as categorical phonetic contrasts, many previous acoustic studies have pointed out that the sibilant space or the space between the constriction points of /s/ and /ʃ/ is continuous in the same axis of front-back articulation (Gunter, Vaughn, & Kendall 2021;Li 2009;Li & Munson 2016). Recent studies showed that the phonetic distinction between /s/ and /ʃ/could be captured by spectral moments analysis which consists of the first spectral moment (M1) or the centroid frequency, the second spectral moment (M2) or the standard deviation of the fricative spectrum, the third spectral moment (M3) or the skewness of the spectral shape, and the fourth spectral moment (M4) or the kurtosis of the spectral shape (Li 2009;Reidy 2016).…”
Section: Tonal Variationmentioning
confidence: 99%
“…( The realization of sibilants was measured by several acoustic parameters, including sibilant duration, F2 value at the onset of the following vowel, and spectral moments analysis of the target sibilant (Li 2009). Although /s/ and /ʃ/ can be identified as categorical phonetic contrasts, many previous acoustic studies have pointed out that the sibilant space or the space between the constriction points of /s/ and /ʃ/ is continuous in the same axis of front-back articulation (Gunter, Vaughn, & Kendall 2021;Li 2009;Li & Munson 2016). Recent studies showed that the phonetic distinction between /s/ and /ʃ/could be captured by spectral moments analysis which consists of the first spectral moment (M1) or the centroid frequency, the second spectral moment (M2) or the standard deviation of the fricative spectrum, the third spectral moment (M3) or the skewness of the spectral shape, and the fourth spectral moment (M4) or the kurtosis of the spectral shape (Li 2009;Reidy 2016).…”
Section: Tonal Variationmentioning
confidence: 99%